Repatriation Adjustment: Proactive Behavior, Perceived Organizational Support And Knowledge Sharing - (:unkn) unknown (University of Jaffna, 2014)
Ineffective management of repatriation of employees is a potential hurdle for better use of top talent and hampers the successful process of internationalization of the organization and can be costly for both repatriates and the organization. This study aims to provide a theoretical model of repatriation adjustment of employees explaining factors that facilitate repatriation adjustment and its consequences based on literature in different disciplines. This study proposed seven propositions and developed a model that was supported by theoretical and empirical evidences. This theoretical model suggests that repatriates’ proactive behavior, perceived coworker support and organizational support facilitates the repatriation adjustment process and repatriates’ adjustment influences repatriate’s knowledge sharing behavior at home organization. Further, it discusses the role of repatriates’ personal and situational variables on adjustment. This study contributes to the literature in a way of providing a meaningful theoretical model explaining the factors that facilitate repatriation adjustment and its consequences, and relates socialization theories to repatriation adjustment. The key practical implications relate to enabling better adjustment of academic repatriates and better use of top talent at the organization.
Keywords: Repatriation; Adjustment; Organization support; Proactive behavior